Hubungan Religiositas dengan Kebahagiaan Masyarakat Sabak Auh Kabupaten Siak - Nurmalis, Nurmalis; Armayati, Leni; Binqalbi Ruzain, Raihanatu (UIR Press, 2022)
This study aimed to determine the relationship of religiosity with the happiness of the people of Sabak Auh District, Siak Regency. Happiness is something that becomes hope in one's life. One of the factors that contribute to happiness is religiosity. This research uses a descriptive research method using a correlation technique, with a random sampling technique. The research samples were 81 people from Sabak Auh District, Siak Regency. The results of the correlation test between the religiosity variable and the happiness variable were significantly 0.000 (p <0.05) which shows positive relationship between these two variables with a correlation value of 0.701. The higher the religiosity, the higher the happiness, conversely the lower the religiosity, the lower the happiness, which means one increases as the other decreases.